THE EFFECT OF SOCIO-ECONOMIC CONDITIONS ON COMMUNITY PARTICIPATION IN PAYING RURAL AND URBAN LAND AND BUILDING TAXES IN MEDAN CITY: (PENGARUH KEADAAN SOSIAL EKONOMI TERHADAP PARTISIPASI MASYARAKAT DALAM MEMBAYAR PAJAK BUMI DAN BANGUNAN PEDESAAN DAN PERKOTAAN DI KOTA MEDAN) - Muhammad Sorimuda Pane; Erika Revida; Muhammad Arifin Nasution (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study analyzes the issue of land and building tax (PBB-P2) in rural and urban areas in Medan City using a socio-economic analysis approach. This approach aims to look at the relationship between social and economic conditions and the level of community participation. The main problem that is the focus of this study is to include the level of community participation in each administrative area in Medan City by combining socio-economic disparity analysis. This study is motivated by factual data related to PBB-P2 which indicates the difference in income in each area of Medan City. This difference indicates a correlation with the socio-economic disparity of the community, especially PBB-P2 is the main supply in Regional Original Revenue (PAD). This study is classified as a type of qualitative research using a descriptive analysis approach. Data collection was carried out by or through interviews, documentation and field observation methods. There are two types of data in this study, including primary sources as the primary source and secondary sources as complementary or reinforcing sources. The results of the study include the relationship between socioeconomic disparities and community participation. Socioeconomic disparities occur due to differences in the significance of income in each region, so that, according to him, this encourages community participation in paying taxes. Then, the behavior pattern of people in paying taxes is also influenced by technological aspects. This can be seen in rural areas where the intensity of community participation in paying taxes is increasing. The information shows that there is a duality relationship between social disparities based on socioeconomic circumstances and technological advances as part of efforts to increase community participation in paying land and building taxes.